Evening versus morning dosing of antihypertensive drugs in hypertensive patients with sleep apnoea. Issue 2 (February 2015) - Kasiakogias, Alexandros; Tsioufis, Costas; Thomopoulos, Costas; Andrikou, Ioannis; Aragiannis, Dimitrios; Dimitriadis, Kyriakos; Tsiachris, Dimitrios; Bilo, Grzegorz; Sideris, Skevos; Filis, Konstantinos; Parati, Gianfranco; Stefanadis, Christodoulos
<x xml:space="preserve">Abstract</x> Objective: Beneficial effects of continuous positive airway pressure (CPAP) on both blood pressure (BP) levels and variability have been documented in patients with obstructive sleep apnoea (OSA). We investigated the relevant impact of different dosing times of antihypertensive drugs beyond CPAP application. Methods: In this prospective, cross-over trial, we included 41 patients with newly diagnosed hypertension and never treated OSA (apnoea-hypopnea index ≥15/h), without increased daytime somnolence (Epworth Score ⩽10 points). Patients first received treatment with valsartan or with a fixed combination of amlodipine and valsartan in a single morning dose for 8 weeks. In the following 8-week period, patients received the same therapeutic regimen in a single evening dose. Office and ambulatory BP were measured at baseline and after each treatment period. Results: Compared with morning administration, evening dosing induced a greater decrease in office SBP (by 3.7 ± 6.5 mmHg, P = 0.001). The decrease in 24-h SBP/DBP was significant and similar after morning and evening dosing (-16.4 ± 11/11.0 ± 7.5 and -18.4 ± 11/12.1 ± 7.5 mmHg, respectively, P < 0.001 for both). Evening compared with morning dosing further reduced night-time SBP/DBP by 4.4 ± 8.6/2.9 ± 5.6 mmHg (P = 0.007 and P = 0.006, respectively). Night-time dippers increased from 24% at baseline to 34% with morning dosing and to 61% with evening dosing. There was no significant interaction between concurrent CPAP application and drugs dosing time on BP changes. Conclusion: Evening dosing of antihypertensive drugs improves night-time BP and dipping status in nonsleepy patients with OSA, irrespective of CPAP application.